Perbandingan Kinerja Local Database Pada Aplikasi Mobile Dengan Flutter - Atmojo, Firman Ali Eka; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Android is currently a popular mobile operating system used all over the world. There are many programming languages ??that can be used to build android applications, one of which is Flutter. Flutter is a Software Development Kit that supports multi platform apps with the Dart programming language developed by Google. Two database management Android supported systems using Flutter are sqflite and HIve. Flutter SDK provides installable packages to install for developers and implements an application that stores its data in this local database. In this study, it is necessary to reveal a comparison of the performance of these two databases. For this reason, an Android application to be used as a test that includes basic data operations that are widely used in this database is implemented in this study. The test results clearly show that in each test with a drastically increased number of data samples Hive provides better performance than sqflite for each type of basic operation.